A rare case of type 4 rapidly progressive glomerulonephritis (atypical) with mesangial IgA deposits: A case report - Puneet Bhuwania (Wolters Kluwer Medknow Publications, 2021)
Rapidly progressive glomerulonephritis can result from glomerular deposition of anti-GBM antibody, immune complexes, or may involve pauci-immune mechanisms. The coexistence of IgA nephropathy, anti-GBM, and anti-neutrophilic cytoplasmic antibodies is unheard of, and the pathogenic role of these antibodies in IgA nephropathy or vice versa remains unclear. Herein, we describe a case of a patient with type 4 rapidly progressive glomerulonephritis who was found to have significant mesangial IgA deposits. The prognosis of this remains unclear but our patient responded well to cytotoxic therapy and plasmapheresis and achieved remission by 6 months. The findings suggest an overlap syndrome of IgA nephropathy-associated type 4 crescentic glomerulonephritis that resembles the former histologically and the latter in its potential to respond to aggressive therapy if detected relatively early in its course.